INTERPRETATIONAL ANALYSIS OF PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK LANGUAGES - Shukurova , Zakhro Farxodovna (Educational Research in Universal Sciences, 2024)
The article is devoted to the interpretational analysis of phraseological units. Furthermore, given paper briefly defines and provides explanations to some of the phraseological linguistic units in different contexts.